2012
DOI: 10.1590/s1806-83242012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory root resorption in primary molars: prevalence and associated factors

Abstract: This study aimed at determining the prevalence of inflammatory root resorption and associated factors in 1068 primary mandibular molars in 453 children 3 to 12 years of age. Age, dental history and medical history were recorded using a questionnaire administered to the children's parents/caregivers. Previously trained and calibrated examiners assessed radiographic images of the primary molars by direct observation, with the aid of a viewing box. Root resorption (physiological or inflammatory), dental crown sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Furthermore, the pattern of force distribution in the PDL and root of the first molar showed that high stress concentration is observed on the root surface at the furcation level, which is in contrast to the canine, which displayed a greater apical concentration. This may explain the high incidence of apical root resorption 25 that appears to occur in the maxillary molar on the root surface at the furcation level, which is difficult to see radiographically in orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pattern of force distribution in the PDL and root of the first molar showed that high stress concentration is observed on the root surface at the furcation level, which is in contrast to the canine, which displayed a greater apical concentration. This may explain the high incidence of apical root resorption 25 that appears to occur in the maxillary molar on the root surface at the furcation level, which is difficult to see radiographically in orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Studies have reported that root resorption in primary teeth depends on the germ of permanent successor as well as other factors. [1,[5][6][7][8] Furthermore, the morphological relationship between the roots of the primary teeth and the crowns of the permanent successors should be considered. [2] In this study, a situation in which the germ of the permanent successor completely occupied only one of the roots of the primary tooth was considered atypical resorption, which may explain the greater prevalence of asymmetrical root resorption in the primary molars of children aged 8-12 years, as primary molars undergo a natural exfoliation process in this period, in comparison to those aged 3-7 years.…”
Section: Discussionmentioning
confidence: 99%
“…These situations of root resorption were associated with areas of periradicular bone rarefactions and tooth decay with pulp involvement, which is in agreement with fi ndings described in previous studies. [1,6,7] It is not possible to identify the initial moment of root resorption clinically or through radiographs. Only advanced stages of root resorption are seen in radiographic exams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory root resorption is not a rare finding in the pediatric community, with spread of infection from a carious tooth as a main cause 2, 3 . In the present case, the interesting finding is that root resorption did not only occur in the carious, necrotic tooth but also occurred in the adjacent vital tooth.…”
Section: Introductionmentioning
confidence: 99%